"Bekerja bersama saya dan bukan untuk saya", dari perspektif komunikasi kepemimpinan dalam Jabatan Kerajaan Malaysia - Syd Zin, Syd Abdul Rahman; Nordin, Mohammed Zin; Osman, Baharudin; Omar, Nuredayu (Universiti Utara Malaysia, 2007)
There are three main objectives in this study.First, to identify the relationships between leadership communication styles (considerateness, openness, supportiveness and participativeness) and satisfaction and commitment of support staff in government departments.Second, to identify which dimension of the leadership communication styles (considerateness, openness, supportiveness and participativeness) is the most effective in influencing the satisfaction and commitment of the support staff in government departments.Third, to identify the differences in the perception of the support staff toward the leadership communication styles of Senior Management Officers/Management and Professional level in government departments based on gender, age and qualification.The study was conducted in government departments throughout Peninsula Malaysia.In the study, leadership communication style was the independent variable and satisfaction and commitment are the dependent variables.Data was obtained from 3,689 respondents comprising of support staff in government departments.Data analysis was done using t-Test, ANOVA, Correlation and Regression.The results were presented descriptively on the background of the respondents, leadership communication styles, satisfaction and commitment.Hypotheses testing were also discussed to answer the objectives of the study.The results showed that there were significant relationships between leadership communication styles (considerateness, openness, supportiveness and participativeness) and satisfaction and commitment of support staff in government departments.It was also found that there was significant influence between leadership communication styles toward satisfaction and commitment of support staff.There were also significant differences in perceptions of support staff toward leadership communication styles of Senior Management Officers in government departments based on gender, age and qualification.This research also suggests for Officers to be given a course and tranning pertaining to leadership communication knowledge.